2019
DOI: 10.4283/jmag.2019.24.2.217
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Magnetic Resonance Signals from Diffusion Weighted Imaging using Compressed Sensitivity Encoding Technique

Abstract: The purpose of this study was to compare image quality between compressed sensitivity encoding (CS) and sensitivity encoding (SENSE) in single-shot turbo spin echo diffusion-weighted imaging (TSE-DWI). Signal-tonoise ratios (SNR), apparent diffusion coefficient (ADC) values, and geometric accuracies were measured with an American College of Radiology head phantom. CS showed a high mean SNR, less variation in ADC values, and reduced imaging acquisition time (21.7 %-39.3 %) compared with SENSE. In addition, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Among them, CS-SENSE has a unique undersampling method of k-space by a balanced incoherent acquisition of variable density with iterative reconstruction. 6,[15][16][17] Recent studies demonstrated that CS-SENSE offers similar image quality to that of SENSE, with a reduction in image acquisition time. 15,[17][18][19] These results are consistent with the current study concerning image quality and image acquisition time reduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, CS-SENSE has a unique undersampling method of k-space by a balanced incoherent acquisition of variable density with iterative reconstruction. 6,[15][16][17] Recent studies demonstrated that CS-SENSE offers similar image quality to that of SENSE, with a reduction in image acquisition time. 15,[17][18][19] These results are consistent with the current study concerning image quality and image acquisition time reduction.…”
Section: Discussionmentioning
confidence: 99%
“…6,[15][16][17] Recent studies demonstrated that CS-SENSE offers similar image quality to that of SENSE, with a reduction in image acquisition time. 15,[17][18][19] These results are consistent with the current study concerning image quality and image acquisition time reduction. However, they had no explanation for phase oversampling distance and did not focus on it for their results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation